Solid Acid Resin Amberlyst 45 as a Catalyst for the Transesterification of Vegetable Oil - Cabral, Natalia Mariano; Lorenti, Juliana P.; Plass, Winfried; Gallo, Jean Marcel R. (Frontiers in Chemistry, 2020)
Commercial transesterification of vegetable oil to biodiesel using alkaline hydroxides requires expensive refined vegetable oil and anhydrous alcohols to avoid saponification. These issues are not present in the acid-catalyzed process; however, the challenge still lies in developing stable and active solid acid catalysts. Herein, Amberlyst 45, a resin for high-temperature application, was efficiently used for biodiesel production by the methanolysis or ethanolysis of vegetable oil. Yields of up to 80 and 84 % were obtained for the fatty acid methyl ester and the fatty acid ethyl ester, respectively. Two processes are proposed and showed to be efficient: (i) incremental addition of alcohol along with the reaction for both methanolysis and ethanolysis; or (ii) one-pot reaction for ethanolysis using oil/ethanol molar ratio of 1/18. The catalytic system used also showed to be compatible with used oil (2.48±0.03 mgNaOH goil-1) and to the presence of water (10-20 wt. % based on the alcohol), allowing the use of waste oil and hydrated alcohol.